'Someone like me': User experiences of the discussion forums of non-12-step alcohol online support groups, June 2019. (November 2019) - Sanger, Sally; Bath, Peter A.; Bates, Jo
Abstract: Background: Peer support is widely acknowledged to be an important factor in recovery from problem drinking. Many seek this from support groups, including those online. Whilst Alcoholics Anonymous (AA) and other 12-step groups have provided help to many people, some individuals do not find them useful. This paper aims to contribute to the current limited knowledge on non-12-step groups, i.e., those that do not follow the approach of AA. Methods: Twenty-five semi-structured interviews were carried out with users of five non-12-step alcohol online support groups (AOSGs) which differed in approach to recovery from problem drinking, size and location. The study was publicised via the groups, and interviewees self-selected. Data were analysed using thematic and template analysis. Results: The most important benefit of the groups, according to most interviewees was finding 'someone like me': something that many did not feel they could do elsewhere, including in AA. Another key perceived difference from 12-step groups was that their groups provided support without requiring them to follow a set programme for recovery. The groups respected individuals' rights to choose their own goal for sobriety (e.g., abstinence, moderate drinking) and to choose how they achieved it. Other key benefits included seeing that recovery is possible and sharing experiential information. Some disadvantages of using the forums are also discussed. Conclusion: The findings report the experiences and perceptions of twenty-five users of non-12-step AOSGs. These are groups that have received little research attention so the findings offer a rare insight into users' opinions on these sources of peer support. Highlights: Peer support is a key part of recovery from problem drinking. Non 12-step-alcohol online support groups are widely available but under-researched sources of support. Many provide support without requiring users to believe in specific recovery programmes. Other benefits for users include finding 'someone like me' which they may not have been able to do in 12-step groups.